2020
DOI: 10.20944/preprints202003.0161.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Small Intestine, an Underestimated Site of SARS-CoV-2 Infection: From Red Queen Effect to Probiotics

Abstract: Understanding how the coronaviruses invade our body is an essential point, and the expression profile of coronaviruses receptor may help us to find where the coronavirus infects our body. We found that the coronavirus receptors, including angiotensin-converting enzyme 2 (ACE2) for SARS-CoV and SARS-Cov-2, are digestion-related enzymes in human enterocytes. Coronaviruses are continually altering the binding receptor and binding modes during their evolution, but the potential target cell in the small intestine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 18 publications
1
45
0
5
Order By: Relevance
“…The epithelial cells of the alveoli serve as a SARS receptor with angiotensinconverting enzyme 2 (ACE2), digestion-related enzymes in human enterocytes. Coronaviruses are frequently varying the binding receptor and binding site during their progression (Feng et al 2020). Viral infection induces alveolar macrophage to form multinucleated giant cells, monocytes, and dendritic cells to act against SARS-CoV.…”
Section: Lung Microbiota and Respiratory Infectionmentioning
confidence: 99%
“…The epithelial cells of the alveoli serve as a SARS receptor with angiotensinconverting enzyme 2 (ACE2), digestion-related enzymes in human enterocytes. Coronaviruses are frequently varying the binding receptor and binding site during their progression (Feng et al 2020). Viral infection induces alveolar macrophage to form multinucleated giant cells, monocytes, and dendritic cells to act against SARS-CoV.…”
Section: Lung Microbiota and Respiratory Infectionmentioning
confidence: 99%
“…Coronaviruses constantly change their binding patterns as they evolve, and the potential target in the lungs also varies, but not in the small intestine, where it remains constant. The cells of the intestinal mucosa (enterocytes) could, therefore, be a reservoir for coronaviruses (1). In the acute phase, only 10% of coronavirus disease 19 (COVID-19) patients present virus cDNA in the blood, but almost 50% of them excrete it in the stools.…”
Section: Introductionmentioning
confidence: 99%
“…There is currently only very limited data available on the COVID-19 induced disturbance in gut microbiota and the possible probiotics role ( Table 1 ). A small case study from a Chinese researcher reported that some COVID-19 patients suffered from microbial dysbiosis with decreased Lactobacillus and Bifidobacterium - the non-pathogenic bacteria yet, preliminary animal studies did not show any correlation between the presence of Lactobacillus acidophilus and Bacillus clausii with the reduction of expression of coronavirus receptor in the murine small intestine as compared with control and post-Salmonella infection models [ 16 , 60 ]. Therefore, irrational use of conventional probiotics should be disregarded in COVID-19 unless we further expand our understanding of SARS-CoV-2 pathogenesis and its effect on gut microbiota and then explore various probiotics' roles in combating COVID-19 with valid evidence.…”
Section: Recent Evidence Of Probiotics In Covid-19 - Preclinical and mentioning
confidence: 99%
“… 1 Targeting the gut–lung microbiota axis by means of a high-fibre diet and probiotics may have anti-inflammatory effects in COVID-19 infection Review [ 157 ] 2 Microbiota Modulating Nutritional Approaches to Countering the Effects of Viral Respiratory Infections Including SARS-CoV-2 through Promoting Metabolic and Immune Fitness with Probiotics and Plant Bioactives Review [ 158 ] 3 Traditional Chinese medicine for COVID-19 treatment Review [ 159 ] 4 Gut microbiota and Covid-19- possible link and implications Review [ 160 ] 5 Probiotics and COVID-19 : one size does not fit all Review [ 161 ] 6 Potential Effects Immunomodulators on Probiotics in COVID-19 Preventing Infection in the Future. A Narrative Review Review [ 162 ] 7 The small intestine, an underestimated site of SARS-CoV-2 infection: from Red Queen effect to probiotics Review [ 60 ] 8 Considering the Effects of Microbiome and Diet on SARS-CoV-2 Infection: Nanotechnology Roles Review [ 163 ] 9 Antiviral effects of probiotic metabolites on COVID-19 Express Communication [ 164 ] 10 Using Probiotics to Flatten the Curve of Coronavirus Disease COVID-2019 Pandemic Review [ 165 ] 11...…”
Section: Recent Evidence Of Probiotics In Covid-19 - Preclinical and mentioning
confidence: 99%